The Present Subjunctive with Retrospective Value in the Peruvian Press - Castro Yauri, Mabel Alelí (2021)
This article analyzes the use of the present subjunctive to express past events in journalistic publications of Peruvian digital newspapers. The aim of the research is to determine whether the favoring of the present subjunctive in the press is influenced by extralinguistic variables such as discursive genre and register. The data have been obtained from 120 digital texts of serious digital newspapers and 30 texts of digital «chicha» newspapers. From a probabilistic analysis, it is concluded that the statistically significant variable is the discursive genre. In addition, informative reports and news are identified as the texts that increase the probability of the use of the present subjunctive.